Burn after Reading: Animal Terrorism in Duncan the Wonder Dog: Show One - Christopher Pizzino (Studies in 20th & 21st Century Literature, 2017)
At present, the tradition of the animal fable remains strong in popular narrative even as the narrative arts, on the whole, remain marginal to the field of animal studies. Duncan the Wonder Dog: Show One, Adam Hines’s 2010 graphic novel, sets a new course for the animal fable and constitutes an unexpected intervention in our conceptions of animals and our relation to them. Hines constructs a world where animals can speak to humans, but are treated much as they are today in the era of the factory farm. He then paints a vivid, complex picture of animal terrorists who resist human oppression. Through his images of animal terrorism, which disrupt the reader’s typical relation to animal fables, Hines not only overturns an ancient tradition of anthropomorphism in narrative, but also challenges some of the assumptions of contemporary animal studies. Duncan the Wonder Dog: Show One thus demands attention as a radical text that exceeds the bounds both of the beast fable and of contemporary philosophy on human-animal relations.
Keywords: Comics studies; Graphic novels; Animal Studies